Protective Potential of Saussurea costus (Falc.) Lipsch. Roots against Cyclophosphamide-Induced Pulmonary Injury in Rats and Its In Vitro Antiviral Effect - Nashwah G. M. Attallah; Amal Kabbash; Walaa A. Negm; Engy Elekhnawy; Reem Binsuwaidan; Omnia Momtaz Al-Fakhrany; Moataz A. Shaldam; Ehssan Moglad; Marwa Tarek; Nehal Samir; Heba M. Fawzy (Pharmaceuticals, 2023)
Diseases and infections of the respiratory tract are common global causes of morbidity and mortality. Our study attempts to elucidate a novel remedy for respiratory ailments, in addition to identifying and quantifying the metabolites of Saussurea costus root extract (SCRE) using HPLC. Then, in vitro antiviral and in vivo lung protective effects were elucidated. The in vitro antiviral potential of SCRE was analyzed via plaque assay against the low pathogenic human coronavirus (HCoV-229E) and human influenza virus (H1N1). The value of the half maximal inhibitory concentrations (IC50) of SCRE against HCoV-229E and H1N1 influenza virus were 23.21 ± 1.1 and 47.6 ± 2.3 µg/mL, respectively. SCRE showed a histological improvement, namely a decrease in inducible nitric oxide synthase (iNOS) and caspase-3 immunoexpression in in vivo cyclophosphamide (CP)-induced acute lung injury (ALI). Moreover, there was a considerable decline in microRNA-let-7a gene expression and a significant rise in heme oxygenase-1 (HO-1) gene expression, with a marked decrease in the malondialdehyde (MDA) level. Molecular docking studies revealed that the major constituents of SCRE have a good affinity for caspase-3, HO-1, and iNOS proteins. In conclusion, a traditional plant SCRE could be a promising source of novel therapeutic agents for treating and protecting respiratory tract diseases. More future investigations should be carried out to reveal its efficacy clinically.